An in-Vitro Study to Compare the Microhardness between Bulk Composite and Fiber Reinforced Bulk Composite: and (Journal of Hama University, 2024)
Aim of study: To Compare the microhardness (HV) between bulk composite and fiber reinforced bulk composite.Materials and methods: This study included 30 cylindrical samples, were randomly divided into two groups in the following order: Group 1 (n=15): Bulk composite (Tetric® N-Ceram Bulk Fill, Ivoclar  Vivadent, USA), and Group 2 (n=15): Fiber reinforced bulk composite (Polydentia, Switzerland). These samples were restored by means of a dark Teflon mold for the research, which contains in its center a cylindrical cavity of dimensions: 5 mm in diameter and 6 mm in height. The samples were photopolymerized using light-curing unit LED (Light Emitting Diode),  an optical intensity of 1200 mw/cm2. The samples were stores at 37° for 24 hours before testing. The microhardness (HV) of the stored samples was tested using microhardness machine (Galileo Durometra, MOD: Isoscan Od). The diamond pyramid head was lowered and pressed on the samples with a force of 50 newton for 15 seconds, then the effect was seen and the maximum diameter was measured under magnification ×40.Results: The values of microhardness (HV) in the fiber reinforced bulk composite group were higher than in the bulk composite group.
Keywords: Bulk Composite, Fiber Reinforced bulk composite, Polyethylene fibers, Microhardness, Diamond pyramid